(untitled) (Journal of Technology and Operations Management, 2015)
The haulage industry in Malaysia at present is facing some problems. The most critical of these problems exists while commercializing businesses which have been exposed to price under cutting and trade liberalization. This experience had been responsible for marginal profit margin in the industry. Both private and government establishments are finding it difficult to sustain their business in the liberalized market. Therefore, the objective of this research is to identify a model which can accommodate haulage businesses in the liberalized market. This study conducted a survey with 170 respondents who are stakeholders in the haulage industry. The findings show that business strategy, administrative activity, financial activity and operation activity are the key antecedents for modeling an open market concept in haulage industry. The model suggested that open market concept in haulage industry increases the revenue of both public and private companies in the haulage industry.